The effect of different doses of caffeine on cardiovascular variables and shooting performance - Ebrahimi, M.; Pordanjani, A. F.; Ahmadabadi, F. (Biomedical Human Kinetics, 2015)
Study aim: the purpose of this study was to assess the effect of 3 mg and 5 mg per kg of body weight of caffeine on heart rate, blood pressure and shooting performance among elite shooters.